THE EFFECT OF THE MODERN AMERICAN LECTURE METHOD ON THE ACHIEVEMENT AND HISTORICAL CULTURE OF FOURTH GRADE LITERARY STUDENTS IN HISTORY - Wissam Aziz Obaid Al-Hamzawy; Dr. Zaid Alwan Abbas Al-Khikani (Scholars Digest Publishing, 2023)
The research aims to learn about the impact of the modern American lecture method in historical culture and attainment among the fourth-grade literary students in history. The experimental curriculum with experimental design was adopted by the two researchers for two equal groups, and they were deliberately selected (prep Abi Dirt for Boys) where it was distributed to two divisions (a). b) The division (a) was selected in a random manner to represent the experimental group and the number of its students (31) students. In the same way, the division (b) was selected to represent the control group and the number of its students (33) students. The research sample reached 64 students. The two researchers were rewarded statistically among the members of the two groups in the following variables: (Chronological age calculated by months, last year's scores for history, intelligence test, historical culture scale) The researchers identified the course in the first four chapters of the History Book of the Fourth Literary Grade. The researchers then formulated behavioural goals, reaching their number. (140) A behavioural objective representing the six levels of knowledge of Bloom's cognitive classification, and for the two research tools, the two researchers prepared an attainment test consisting of (40) Objective test paragraph of multi-quadrilateral choice of alternatives according to (standard table), the historical culture scale of (30) paragraphs, and verification of the coefficient of honesty, the coefficient of discrimination, difficulty and stability; Its stability has been verified in a halfway form of fragmentation; The researchers used appropriate statistical means to extract data, and the results showed that the pilot group's students outperformed the control group's students.
Keywords: Modern American Lecture Method, Educational Achievement, History Subject.